Are Elites Meritocratic and Efficiency-Seeking? Evidence from MBA Students - Preuss, Marcel (2025)
Elites disproportionately influence policymaking, yet little is known about their fairness and efficiency preferences—key determinants of support for redistributive policies. We investigate these preferences in an incentivized lab experiment with a group of future elites—Ivy League MBA students. We find that MBA students implement substantially more unequal earnings distributions than the average American, regardless of whether inequality stems from luck or merit. Their redistributive choices are also highly responsive to efficiency costs, with an elasticity an order of magnitude larger than that found in representative U.S. samples. Analyzing fairness ideals, we find that MBA students are less likely to be strict meritocrats than the broader population. These findings provide novel insights into how elites’ redistributive preferences may shape high levels of inequality in the U.S.